Breast Cancers With Magee Equation Score of Less Than 18, or 18-25 and Mitosis Score of 1, Do Not Require Oncotype DX Testing: A Value Study. Issue 3 (2nd November 2018) - Bhargava, Rohit; Clark, Beth Z; Dabbs, David J
Abstract: Objectives: To investigate use of Magee equations (MEs) to determine which breast cancer cases can be excluded from Oncotype DX testing. Methods: A prospective value study was carried out using data from pathology reports. Results: If all three MEs scores were less than 18 or 31 or higher, the cases were labeled do not send for testing. If any or all scores were 18 to 25, cases were labeled do not send if mitosis score was 1. Of the total 205 cases, 146 (71%) were labeled do not send; of these, the correct call was made in 143 (98%) cases. Two of the three discordant cases had associated nontumor factors, likely resulting in higher scores. Conclusions: Cases with ME scores less than 18, or 18 to 25 and mitosis score 1, do not require Oncotype DX testing, an estimated saving of US280, 000 per 100 clinical requests.